Evaluating local livelihoods, sustainable forest management, and the potential for ecotourism development in Kaimur Wildlife Sanctuary, India - Bhushan, Shashi; Dincă, Iulian; Shikha, Shalini (Frontiers in Forests and Global Change, 2024)
Effective forest management in India must address the economic needs of local communities, often displaced by restrictive policies. These marginalized local communities, despite their traditional knowledge, lack alternative income sources, necessitating integration into management or exploration of options like ecotourism. Recognized for balancing conservation and livelihood support, ecotourism offers a viable solution to enhance economic opportunities while conserving resources. This paper explores ecotourism’s potential to boost local economies and examines how current management practices and alternative livelihoods can address resource scarcity in Kaimur Wildlife Sanctuary, India. The study employed a combination of qualitative research methods, including semi-structured interviews, surveys, on-site observations, focus group discussions, and literature reviews, along with a cross-sectional survey approach that integrated both qualitative and quantitative data collection to provide comprehensive insights. The study reveals that impoverished communities near forests, reliant on indigenous knowledge and resources, have been severely affected by forest degradation and current management practices. The findings highlight community-based ecotourism as a promising solution for sustainable income generation in the region, helping to mitigate resource degradation and support sustainable development. However, the region’s ecotourism potential is hindered by inadequate infrastructure, training & opportunities, and public awareness. Developing ecotourism as an alternative income source, alongside an inclusive forest management strategy that integrates social diversity, livelihood generation, and conservation, is essential for promoting nature conservation, reducing poverty, and enhancing the well-being of local communities. Strengthening non-agricultural livelihoods and preserving indigenous knowledge through ecotourism is crucial for effective resource management, while the study underscores the importance of community involvement in forest governance, offering valuable insights for policymakers and conservationists in developing sustainable management strategies.